RISK SCORE PREDICTION MODEL FOR DEMENTIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS : AN UPDATE SYSTEMATIC REVIEW - Suwandhi; Ayyub (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Dementia is a substantial global health issue. Reduction in future numbers of dementia cases through effective preventive strategies could significantly affect the personal and socioeconomic burdens of dementia. WHO has recommended that countries urgently develop national public health programmes to reduce the impact of dementia. The aim: The aim of this study to show about risk score prediction model for dementia in patients with type 2 diabetes mellitus. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 67 articles, whereas the results of our search on SagePub get 210 articles, on Google Scholar 1350 articles. Records remove before screening are 667, so we get 960 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: RxDx-Dementia risk index to predict dementia in patients with type 2 diabetes and hypertension. The RxDx-Dementia risk index which incorporated diagnosis and prescription-based information in a single summary score performed better than diagnosis- or prescription-based comorbidity scores or its combinations. The RxDx-Dementia risk index can be used for prognostic purpose or to control confounding in epidemiological studies.